Interreligious relations : biblical perspectives : proceedings from the second Norwegian Summer Academy of Biblical Studies (NSABS), Ansgar University College, Kristiansand, Norway, August 2015 /: biblical perspectives : proceedings from the second Norwegian Summer Academy of Biblical Studies (NSABS), Ansgar University College, Kristiansand, Norway, August 2015. (2017) - Unknown
No abstract available